Relative reactivity of saturated hydrocarbons during thermochemical sulfate reduction. (1st October 2019) - Cai, Chunfang; Tang, Youjun; Li, Kaikai; Jiang, Kaixi; Jiang, Chunqing; Xiao, Qilin
Graphical abstract: Pr and Ph are preferentially oxidized compared to n C17 and n C18, leading to decrease in Pr/ n C17 and Ph/ n C18 ratios with thiaadamantanes concentrations, a measure of the extent of TSR in Tazhong oils and condensates. Highlights: TSR does not preferentially deplete triterpanes and α, β hopanes over Ts. Pr and Ph are preferentially oxidized over n C17 and n C18 . i C4 was preferentially depleted over n C4 only during earlier TSR stage. Relative oxidization sequence during TSR overlaps significantly. Abstract: Tazhong and four other well-known TSR-altered petroleum reservoirs from around the world were analyzed for their molecular and carbon isotopic compositions of saturated hydrocarbons, thiaadamantanes concentrations or H2 S contents to determine the relative stability of saturated hydrocarbons during thermochemical sulfate reduction (TSR). We find that TSR does not preferentially deplete tricyclic terpanes and 17α, 21β hopanes with the "exposed" tertiary carbon atoms compared to 18α (H)-22, 29, 30-trisnorhopane (Ts) and C29 Ts that have no tertiary carbon atoms, as proposed by Xia and Gong [35] . However, pristane (Pr) and phytane (Ph) seem to have been preferentially oxidized over normal C17 and C18 alkanes, respectively, resulting in decreasing Pr/ n C17 and Ph/ n C18 ratios with increasing extent of TSR for the Tazhong and Nisku oils and condensates. i C4 appears to be preferentially depleted relative to n C4 during early TSR stage. At later TSR stage both n C3 and n C4 are oxidized more readily than i C4 in the Mobile Bay Norphlet Formation condensates. Thus, we tentatively propose that relative oxidization order during TSR may start with long chain iso -alkanes followed by n -alkanes, then cycloalkanes, C2 -C4 alkanes and finally methane; however, it seems that oxidization of these compounds overlaps significantly.